A study of Acinetobacter infections in a tertiary care hospital in Northeast India - Saha, Swarnatrisha; Devi, Ksh Mamta; Damrolien, Shan; Devi, Kh Sulochana (International Journal of Research in Medical Sciences, 2018)
Background: Acinetobacter is an important opportunistic pathogen and is a common cause of hospital acquired infections. Acinetobacter infections are often extremely difficult to treat because of their widespread resistance to the major groups of antibiotics. The study was conducted to determine prevalence and antibiotic susceptibility pattern of Acinetobacter species isolated from various clinical samples. Methods: Clinical specimens over a period of 2yrs from May 2015 to April 2017 were collected from the patients attending the hospital. Acinetobacter species isolates were identified, and antibiotic susceptibility test was done following standard operative procedures. Results: From 9979 clinical specimens, 3715 were positive for significant bacterial growth of which 111 (2.9%) were culture positive for Acinetobacter spp. Among 111 isolates 109 (98.2%) isolates were Acinetobacter baumanni and 2 (1.8%) were Acinetobacter lwoffii. Maximum isolates were isolated from urine samples 36 (32.4%) and majority of the isolates were from wards (56.7%) giving a probability of increased hospital acquired infections. Maximum resistance was shown by cefipime (80.1%). Imipenem and Meropenem shows resistance of 25.3% and 29.7% respectively. ICU isolates showed extensive resistance in comparison to wards and OPD. Conclusions: Increasing trend of resistance pattern to a large range of antibiotics is a matter of concern. To avoid resistance, antibiotics should be used judiciously, and empirical therapy should be determined for each hospital according to the resistance rates of the hospital. Infection with MDR Acinetobacter species is independently associated with high mortality, emphasizing the need for aggressive infection control strategies.